(x-6)(x-6)=(x+6)(x-12)

Simple and best practice solution for (x-6)(x-6)=(x+6)(x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x-6)=(x+6)(x-12) equation:


Simplifying
(x + -6)(x + -6) = (x + 6)(x + -12)

Reorder the terms:
(-6 + x)(x + -6) = (x + 6)(x + -12)

Reorder the terms:
(-6 + x)(-6 + x) = (x + 6)(x + -12)

Multiply (-6 + x) * (-6 + x)
(-6(-6 + x) + x(-6 + x)) = (x + 6)(x + -12)
((-6 * -6 + x * -6) + x(-6 + x)) = (x + 6)(x + -12)
((36 + -6x) + x(-6 + x)) = (x + 6)(x + -12)
(36 + -6x + (-6 * x + x * x)) = (x + 6)(x + -12)
(36 + -6x + (-6x + x2)) = (x + 6)(x + -12)

Combine like terms: -6x + -6x = -12x
(36 + -12x + x2) = (x + 6)(x + -12)

Reorder the terms:
36 + -12x + x2 = (6 + x)(x + -12)

Reorder the terms:
36 + -12x + x2 = (6 + x)(-12 + x)

Multiply (6 + x) * (-12 + x)
36 + -12x + x2 = (6(-12 + x) + x(-12 + x))
36 + -12x + x2 = ((-12 * 6 + x * 6) + x(-12 + x))
36 + -12x + x2 = ((-72 + 6x) + x(-12 + x))
36 + -12x + x2 = (-72 + 6x + (-12 * x + x * x))
36 + -12x + x2 = (-72 + 6x + (-12x + x2))

Combine like terms: 6x + -12x = -6x
36 + -12x + x2 = (-72 + -6x + x2)

Add '-1x2' to each side of the equation.
36 + -12x + x2 + -1x2 = -72 + -6x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
36 + -12x + 0 = -72 + -6x + x2 + -1x2
36 + -12x = -72 + -6x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
36 + -12x = -72 + -6x + 0
36 + -12x = -72 + -6x

Solving
36 + -12x = -72 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
36 + -12x + 6x = -72 + -6x + 6x

Combine like terms: -12x + 6x = -6x
36 + -6x = -72 + -6x + 6x

Combine like terms: -6x + 6x = 0
36 + -6x = -72 + 0
36 + -6x = -72

Add '-36' to each side of the equation.
36 + -36 + -6x = -72 + -36

Combine like terms: 36 + -36 = 0
0 + -6x = -72 + -36
-6x = -72 + -36

Combine like terms: -72 + -36 = -108
-6x = -108

Divide each side by '-6'.
x = 18

Simplifying
x = 18

See similar equations:

| (x-1)(x+1)=(x-5)(x+9) | | 5w+9=9w+33 | | -35=-11-3(y-1) | | x+3/(-6)=3 | | 216=2(2x)+2(x) | | 0.4t^4+7.72t^3-44.02t^2+476.9t= | | (x+11)(x-3)=(x+7)(x+9) | | 2(3x-1)=18 | | (x+2)*(x-7)=0 | | 3*-4-7=-5*-4-39 | | 22+2x=6x+62 | | -80=8(3x-1) | | -2(x+12)=18 | | 3x+2=130-x | | -7(x-9)=-14 | | -5x=20+-7x | | 3x+28-(6-x)=-38 | | 7-2n=19 | | z^2+4z+z=0 | | 8(x-4)=12 | | (3)x*x+11x+6=0 | | 2-3(x-5)=-7(x+1) | | 100-2m= | | 5x-10-4x+15=45 | | 3x*3x+11x+6=o | | 2[5-(x-12)]=x-14 | | 3y-7=-5y-39 | | x-.85x=84 | | 2(x-5)-5(7-x)=9 | | 6(2x+1)=3x-7x | | (3z+7)(3-z)=0 | | 3y-9=24+3y |

Equations solver categories